DESIGN AND CONSTRUCTION OF A POTENTIOSTAT FOR MATERIAL SYNTHESIS PROCESS USING CHEMICAL ELECTRODEPOSITION - Diego F. Gómez; Andrés Rosales-Rivera; Alvaro Gómez-Peña (Momento, 2011)
This work focuses on the design and development of a potentiostat, which can be used in different areas including synthesis of materials by chemical electrodeposition, studies of corrosion processes and tests of cyclic voltammetry. The developed potentiostat is versatile, stable, operates in the range of micro-ampere and pro-vides high performance as a commercial potentiostat but is lowest cost. Operational amplifiers featuring low currents of polarization, high impedance input and low offset voltage, as well as simulation of real resistance loads were used in the construction of the potentiostat. This potentiostat was used to characterize the process of redox occurring in the chemical electrodeposition of PD on a substrate. Voltammetry and final deposition results are comparable with results reported in the literature for the palladium.